Ulama Birokrat: Kiprah Abuya TB. Abdul Halim Kadu Peusing dalam Memperjuangkan Banten - Siti Nur Immamah; H. S. Suhaedi; Erdi Rudjikartawi (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
The role of ulama is very important for the community in protecting the interests of the community. Ulama occupy an important position in the moral formation of society, even during the colonial period. Ulama leadership in the world of politics was very influential in the struggle against Dutch colonialism in Banten. The position of the ulama is inseparable from the prevailing tradition in the santri community, especially in rural areas which assume that in religion someone must follow what has been passed down by the ulama. Abuya Tb. Abdul Halim was a very charismatic cleric and his influence was very large for the people of Pandeglang. He was born around 1889 in Kadu Peusing Village, Kabayan Village, Pandeglang Subdistrict, Pandeglang Regency. The struggle of Abuya Tb. Abdul Halim started since he built Islamic boarding schools, Abuya thoughts Tb. Abdul Halim was very influenced by Sheikh Nawawi Tanara because Abuya Tb.Abdul Halim had studied with Sheikh Nawawi Tanara. The spirit of his struggle was poured out by participating in religious meetings, practicing his knowledge and supporting organizations such as Masyumi and NU. In 1945 Abuya Tb. Abdul Halim appeared in the struggle against the Dutch colonial until he was appointed Regent in Pandeglang in 1945-1947.